2018
DOI: 10.1080/16549716.2018.1527971
|View full text |Cite
|
Sign up to set email alerts
|

Do women’s perspectives of quality of care during childbirth match with those of providers? A qualitative study in Uttar Pradesh, India

Abstract: Background: Persistently high maternal mortality levels are a concern in developing countries. In India, monetary incentive schemes have increased institutional delivery rates appreciably, but have not been equally successful in reducing maternal mortality. Maternal outcomes are affected by quality of obstetric care and socio-cultural norms. In this light there is need to examine the quality of care provided to women delivering in institutions. Objective: This study aimed to examine pregnant women’s expectatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 52 publications
2
49
1
Order By: Relevance
“…The study also revealed that midwives attributed their professional misconduct during intrapartum care to the unwillingness of childbearing women to yield to their instructions. This victim blaming attitude of the midwives have been reported in another study conducted in India in which midwives blamed some of their disrespectful and abusive care practices on non-cooperative attitudes of women who visited the hospital for care [29].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The study also revealed that midwives attributed their professional misconduct during intrapartum care to the unwillingness of childbearing women to yield to their instructions. This victim blaming attitude of the midwives have been reported in another study conducted in India in which midwives blamed some of their disrespectful and abusive care practices on non-cooperative attitudes of women who visited the hospital for care [29].…”
Section: Discussionsupporting
confidence: 56%
“…From a meta-ethnographic study, it is evident that midwives in the United Kingdom (UK) were aware of childbearing women's rights to autonomy but were often faced with a dilemma when childbearing women make birth position choice outside recommended guidelines [23]. Additional cited reasons for the compromise of quality and respectful intrapartum care as reported by Indian providers were noncooperative attitudes of childbearing women and their family as well as structural layout of labour units which does not ensure privacy in labour [29].…”
Section: Introductionmentioning
confidence: 99%
“…While it is possible that visual and auditory privacy was maintained during these visits such as conceptualized in global normative documents (2,46,47), it is also possible that women in Bangladesh conceptualize privacy differently and that their expectations of privacy are maintained even if others, particularly women, can see and hear them during the visit. Alternatively, it is possible that due to the prior experience in public health facilities or prior knowledge about the service delivery process in these facilities, women accepted those aspects challenging their privacy during ANC consultations (48). Women's understandings, expectations and preferences around privacy should be explored to design actions to promote privacy which articulates with their conceptualizations and desires.…”
Section: Discussionmentioning
confidence: 99%
“…This study sought to establish the determinants of utilization of 5 maternal health care services among maternity clients in the HWSWD. Improving utilization of ANC services, institutional delivery services as well as PNC services is an integral approach to achieving greater reductions in maternal and neonatal morbidity and mortality as well as reduction of costs of associated complications to the health sector [14]. Figure 2.…”
Section: Introductionmentioning
confidence: 99%